LAYANAN BIMBINGAN KARIER TERHADAP PERENCANAAN KARIER PESERTA DIDIK DI SMA - Farida Farida; Teti Sobari; Rima Irmayanti (IKIP Siliwangi, 2020)
The purpose of this study was to obtain the implementation of career guidance services on the career planning of students in class XII IPA, the response of students at the time of implementation after being given career guidance and to find out the obstacles of students during the implementation of career guidance. This research is descriptive qualitative. The methods used in this research are interviews, observation, and documentation. The subjects in this study were the Counseling Guidance Teacher and 6 students of class XII IPA SMA Negeri 16 Garut. The results showed that career guidance services were needed to assist students in planning their careers. After attending career guidance services students have a new picture or insight in the world of careers, there is motivation or encouragement in finalizing career planning, and can better recognize the talents that exist within themselves, so there is no mistake in determining career planning.Keywords: Career Guidance, Career Planning